INCREASING THE LEVEL OF ECONOMIC GROWTH IN UZBEKISTAN (Proceedings of International Educators Conference, 2023)
In this article, a brief history of economic growth in the Republic of Uzbekistan, the years of development, the opinions of the World and Asian banks about the level of economic growth in Uzbekistan, the impact of the Ukrainian-Russian conflict on Uzbekistan and Asian countries. about and Gross Domestic Product (GDP) growth levels and years. Experiences of developed countries in economic growth, as well as proposals and conclusions related to the sector are discussed.